Empirical Modelling of Public Lighting Emission Functions - Espey, Brian (My University, 2021)
Study of light at night has increased in recent decades due to the recognition of its impact on the environment, potential health concerns, as well as both the financial and carbon cost of energy waste. The advent of more extensive and improved ground-based measurements together with quantifiable satellite data has revolutionised the field, and provided data to test improved theoretical models. However, “closing the loop” and finding a detailed connection between these measurements requires knowledge of the “city emission function”, the angular distribution of upwelling radiation with zenith distance. Simplified analytical functions have been superseded by more complex models involving statistical approximation of emission sources and obstructions and inversion techniques now permit the estimation of emission functions from the observed sky brightness measurements. In this paper, we present an efficient GIS-based method to model public lighting using real-world photometric data and high-resolution digital elevation maps of obstructions such as buildings and trees at a 1 m scale. We discuss the results of this work for a sample of Irish towns as well as a city area. We also compare our results to previous emission functions as well as to observed asymmetries in emission detected by satellites such as SUOMI VIIRS.
PUBLISHED
Keywords: Artificial light at night (ALAN); Light pollution; Public lighting; City emission function (CEF); Urban emission; Satellite data; VIIRS DNB; Lantern photometry; Digital elevation models; Smart & Sustainable Planet; GIS modelling; Light Pollution; Physics; Environment and housing